Interaction of Work-Life Balanced and Self-Efficacy on Employee Performance - Josephus Noya (Publikasi Indonesia, 2024)
This research aims to determine, test and analyze the influence of work-life balance and self-efficacy on the performance of Maluku Province Bappeda employees. This research uses a descriptive-quantitative approach with a correlational cause-effect type. A total of 108 people were determined using full sampling. Data were analyzed using multiple linear regression with the help of SPSS 23.00 software. The results of the study concluded that (1) work-life balance had a positive and significant effect on the performance of Maluku Province Bappeda employees, (2) self-efficacy had a positive and significant effect on the performance of Maluku Province Bappeda employees and (3) work-life balance and self-efficacy simultaneously have a positive and significant effect on the performance of Maluku Province Bappeda employees.